COMPETENCY ASSESSMENT SEBAGAI INSTRUMEN PENGUATAN SISTEM MERIT DALAM MANAJEMEN TALENTA ASN DI PEMERINTAH PROVINSI SULAWESI SELATAN - Firdaus, Riska; Muhammad Yunus; Muhammad Rusdi (Jurnal Ilmiah Administrasita', 2025)
Improving the quality of human resources in the civil service is an important part of bureaucratic reform that emphasizes the application of a merit system in filling positions. Competency Assessment is a strategic instrument for assessing the potential, performance, and suitability of employees to the needs of the organization in an objective and measurable manner. This study aims to analyze the implementation of Competency Assessment in the South Sulawesi Provincial Government as part of a merit-based talent management system. The research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, non-participant observation, and documentation studies at the Regional Civil Service Agency (BKD), Human Resource Development Agency (BPSDM), and Organization Bureau. Data analysis was conducted thematically based on the Miles, Huberman, and Saldaña (2019) model. The results show that Competency Assessment has been integrated into a digital talent pool system based on the Nine-Box Talent Matrix to map the potential and performance of ASN. However, the implementation of the assessment is still limited to a small number of employees and has not become the main basis for filling strategic positions. In addition, follow-up on assessment results through coaching feedback activities has not been consistent due to budget and resource constraints. This study recommends a gradual expansion of the scope of assessment, optimization of the use of assessment data in career development, and strengthening of inter-agency coordination in ASN talent management to create a professional, adaptive, and performance-oriented bureaucracy.